3T MRI of the breast with computer aided diagnosis, can it help to avoid unnecessary invasive procedures???. Issue 1 (1st March 2016) - Agha, Mahmoud; Eid, Ahmed Fathi; Nouh, Mohamed
Abstract: Objective: This study aimed to check the sensitivity of multiple newly developed 3T MRI breast sequences using CAD software, in pre-sampling diagnosis of breast cancer, in an attempt to minimize unnecessary invasive sampling or surgical procedures. Patients and methods: This was a prospective study, included 120 female patients, presented with debatable or malignancy suspected mammo-sonographic results. The study protocol was approved by the ethics committee in Al-Mana General Hospital. Results: 36 patients' tumors were reported as benign and 84 were reported as malignant. Biopsy approved 33 tumors as benign and 87 as malignant tumors. These results gave indices of 93.1% sensitivity and 90.9% specificity. Conclusion: 3T MRI breast with CAD is very sensitive imaging tool, that can help to avoid unnecessary invasive procedures.